Effects of low-intensity shivering on energy metabolism during exercise in the cold - Gagnon, D. D.; Kyröläinen, H.; Herzig, K. H.; Gagnon, S. S.; Rintamäki, H. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Metabolically, shivering and exercise are not analogous processes (Tipton et al. 1989) as shivering relies more heavily on carbohydrates (CHO) as fuel (Haman et al 2005). Inconsistent findings in energy metabolism during submaximal exercise in the cold may partly be explained by the appearance of shivering which preferentially recruits type II muscles fibers. Therefore, the purpose of this study was to examine the influence of low-intensity shivering (LIS) on energy metabolism during exercise in the cold. Methods: Nine male subjects, dressed in shorts and t-shirt, exercised on 4 separate days. Subjects entered a climatic chamber set at 0°C, then exercised for 60-min on a treadmill or, sat during a cooling period, prior to exercise, until LIS was induced (40% of shivering peak [..15% VO2max]). Exercise was performed at 50% and 70% of maximal oxygen uptake in both LIS and non-shivering control (CON) conditions. Core temperature (Tcore), weighted mean skin temperature (Tskin), heart rate (HR), and respiratory quotient (RQ) values were averaged over the last 10-min of every 15-min period during exercise. Blood samples were collected before entering the chamber (baseline) and at 30- and 60-min to measure serum non-esterified fatty acids (NEFA), glycerol (GLY) and glucose (GLU). Data was analyzed using a three-way ANOVA (factors: shivering, exercise intensity and time) for repeated measures with significance at p<0.05. Results: Both Tcore and Tskin indicated lower values in LIS compared to CON within both exercise intensities from 15- to 45-min (p<0.05). HR was lower in LIS (129± 10bpm) compared to CON (137±10bpm) in the first 15-min of exercise only (p<0.05). NEFA and GLU were not affected by shivering (p=0.91). Meanwhile, GLY concentration was greater in LIS (0.39±0.13mmol/L) vs. CON (0.31±0.11mmol/L) at 70% VO2 (p<0.05). Finally, shivering did not modulate the RQ response across time or intensities (LIS 0.87±0.04 vs. CON 0.86±0.04, p=0.84). Conclusion: LIS combined with submaximal exercise influenced Tcore, Tskin, HR and GLY, mostly in the early stage of exercise. Nonetheless, energy sources remained unaffected. The increase in CHO reliance from shivering was likely concealed by its limited contribution to total muscle activity and its partial inhibition from exercise. Future work should address higher intensities of shivering and lower levels of activity to examine possible interactions between both processes.